2021
DOI: 10.1007/s10237-021-01422-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive prediction of the mouse tibia mechanical properties from microCT images: comparison between different finite element models

Abstract: New treatments for bone diseases require testing in animal models before clinical translation, and the mouse tibia is among the most common models. In vivo micro-Computed Tomography (microCT)-based micro-Finite Element (microFE) models can be used for predicting the bone strength non-invasively, after proper validation against experimental data. Different modelling techniques can be used to estimate the bone properties, and the accuracy associated with each is unclear. The aim of this study was to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 50 publications
4
30
0
Order By: Relevance
“…The use of heterogeneous material properties would help to understand the role of TMD changes in strain distribution, but would alter the strain profile especially in the trabecular regions (Webster et al, 2012). However, this was not conducted due to the small increment to predictions of structural failure in the murine caudal vertebra (Webster et al, 2012) and mouse tibia (Oliviero et al, 2021b) at the expense of a large computational cost. Although the use of tetrahedral mesh would capture the strain distribution at the surface more smoothly in principle (Cheong et al, 2020a,b), both hexahedral and tetrahedral models of the mouse tibia were found to yield similar results in stiffness, failure load and local strain distributions in the cortical bone (Oliviero et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of heterogeneous material properties would help to understand the role of TMD changes in strain distribution, but would alter the strain profile especially in the trabecular regions (Webster et al, 2012). However, this was not conducted due to the small increment to predictions of structural failure in the murine caudal vertebra (Webster et al, 2012) and mouse tibia (Oliviero et al, 2021b) at the expense of a large computational cost. Although the use of tetrahedral mesh would capture the strain distribution at the surface more smoothly in principle (Cheong et al, 2020a,b), both hexahedral and tetrahedral models of the mouse tibia were found to yield similar results in stiffness, failure load and local strain distributions in the cortical bone (Oliviero et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not conducted due to the small increment to predictions of structural failure in the murine caudal vertebra (Webster et al, 2012) and mouse tibia (Oliviero et al, 2021b) at the expense of a large computational cost. Although the use of tetrahedral mesh would capture the strain distribution at the surface more smoothly in principle (Cheong et al, 2020a,b), both hexahedral and tetrahedral models of the mouse tibia were found to yield similar results in stiffness, failure load and local strain distributions in the cortical bone (Oliviero et al, 2021b). Moreover, simple loading was applied to quantify the changes to the micromechanical properties, rather than determine the mechanical environment induced by the loading.…”
Section: Discussionmentioning
confidence: 99%
“…A connectivity lter (connectivity rule = 6, bwlabeln function in Matlab) was used to remove from the binary image the unconnected bone islands and the connected bone voxels were converted into 8-node hexahedral elements. Bone was considered homogenous, isotropic, and linear elastic, with a modulus of elasticity of 14.8GPa, and Poisson's ratio of 0.3 14,30 . Uniaxial compression was applied by xing the nodes of the most distal section of the model and by applying an axial displacement equal to 0.1mm at the proximal end.…”
Section: Micro-nite Element Analysismentioning
confidence: 99%
“…The 10% of the total tibia length was excluded from this analysis at each extremity of the model to reduce the boundary effects. These models have been recently validated against state-of-the-art experiments for the prediction of local deformation and structural properties 14,30 . The resulting linear microFE models were solved (Ansys, Release 15.0, ANSYS, Inc.) on a high-performance computing (HPC) system (ShARC, University of She eld; 8 cores, memory = 32GB/core) in approximately 30 minutes.…”
Section: Micro-nite Element Analysismentioning
confidence: 99%
See 1 more Smart Citation